Barriers to Mental Health Service Accessibility Among University Students in Malawi: A Qualitative Multi-Stakeholder Study - Shakira Kachingwe; Kizito Chimowa; Alfred S. Hara (American Journal of Educational Leadership & Policy Studies, 2026)
Background: Mental health challenges among university students represent a growing public health concern across sub-Saharan Africa. Despite documented high rates of depression, anxiety, and psychological distress in this population, the accessibility of mental health services within Malawian higher education institutions remains largely uninvestigated. Objectives: This study explored barriers to mental health service accessibility among university students at Emmanuel University in Lilongwe, Malawi. Methods: A qualitative research design was employed, guided by Andersen’s Behavioral Model of Health Service Utilization (BMHSU) and the Framework for Access to Mental Health Services (FAMS). Purposive sampling was used to recruit 12 participants: eight students, two lecturers, one university administrator, and one mental health professional. Data were collected through semi-structured interviews and a focus group discussion and analysed using Braun and Clarke’s (2006) thematic analysis, producing 42 initial codes consolidated into five overarching themes. Results: Five themes emerged: (1) a visibility-utilisation gap in service accessibility; (2) multilayered mental health stigma rooted in cultural, religious, and institutional dynamics; (3) academic pressure operating as a structural stressor tied to financial and social consequences; (4) informal support systems that were well-intentioned but clinically inadequate; and (5) a policy-practice gap in mental health awareness and communication. A marked divergence was identified between administrators’ confidence in existing provision and the persistent inaccessibility reported by students and lecturers. Conclusions: Structural, psychosocial, and institutional barriers collectively constrain mental health service accessibility. Addressing them requires targeted anti-stigma interventions, strengthened professional counselling systems, formal institutional policies, and active communication strategies that close the gap between policy existence and lived student experience.